Removing Cemented Dual Mobility Liners From Acetabular Components: A Technical Tip for a Challenging Surgical Problem - Jacob M. Wilson, MD; Aleksander Mika, MD; J. Ryan Martin, MD (Arthroplasty Today, 2023)
Dislocation remains the leading cause of failure following revision total hip arthroplasty. Dual mobility (DM) constructs, including monoblock cups designed for cementation, reduce but do not eliminate this risk. Cemented DM constructs offer several unique advantages in revision total hip arthroplasty, and as such, they have gained popularity. Despite their advantages, a portion of these implants will require revision for infection or recurrent dislocation. Removal of a cemented DM cup presents numerous challenges, and there is no effective published technique. Here, we present an effective technique for the safe removal of one design of cemented DM cup.